The socialization preventions underage marriage according to Marriage Law No. 16 of 2019 - M. Yusuf Khummaini; Nastangin Nastangin (Penamas: Journal of Community Service, 2026)
Marriage Law No. 16 of 2019 stipulates the minimum age for marriage as 19 years for both men and women. In reality, many people in society still marry before reaching the minimum age for marriage. The purpose of this community engagement is to provide information to the community on preventing underage marriage and the minimum age for marriage under Marriage Law No. 16 of 2019. This community engagement is in the Getasan District, Semarang Regency. There were 35 participants in the community engagement. This community engagement uses a Participatory Action Research (PAR) approach, often known as the PAR method. This approach includes planning, action, observation, and reflection. The results of this community engagement program show that the socialization prevention of underage marriage can be considered successful and in line with planned targets. This is an evident fact that after participating in this socialization program, the participants were able 100% to understand the minimum age limit for marriage in the Indonesian Marriage Law No. 16 of 2019, which is 19 years old for both men and women.